IMPLEMENTATION OF ISLAMIC VALUES IN INDONESIAN POLITICAL DYNAMICS - Yohana Oktaviani Lavan (Intelegensia : Jurnal Pendidikan Islam, 2021)
Islam and politics are closely related, Islam puts politics as one way to protect Muslims. Islam without politics will give birth to Muslims who do not have the freedom and freedom to implement Islamic law. Likewise, politics without Islam will only give birth to a society that glorifies power, position, and worldliness. So it is necessary to apply Islamic values in politics, especially in Indonesia, because they can be used as a reference in carrying out the dynamics of politics in Indonesia. The existence of Islamic organizations with political nuances that emerged during the movement until now in their development have implemented Islamic values. So at this time it is necessary to review how the application and development of Islamic values in politics in Indonesia so as not to deviate from the teachings of Islam. The method used in this research is discourse analysis with a qualitative approach. The data collection techniques used were library research and literature studies. The purpose of writing this research is to find out and explore the implementation of Islamic values in the dynamics of politics in Indonesia, this will be discussed and become the focus of this paper.